Diversity of longicorn beetles (Coleoptera: Cerambycidae) associated with a mangrove swamp in Tabasco, Mexico - Gerónimo-Torres, • José del Carmen; Álvarez-Ramón, • Óscar Iván; Ríos-Rodas, Liliana; Sánchez-Díaz, • Baltazar; •Sánchez-Gutiérrez, • Facundo; Pérez-De la Cruz, Manuel (Revista de Biología Tropical, 2024)
Introduction: The mangrove is one of the most important ecosystems on the planet, due to the ecological role it plays on coastlines, it provides development, protection, and feeding areas for various species. Objective: To determine the diversity and annual fluctuation of the cerambycid community, as well as the vertical distribution of species richness associated with the edge and interior of a mangrove in Tabasco, Mexico. Methods: The sampling was carried out from August 2016 to July 2017. The capture of insects was performed with interception traps baited with ethanol 70 % at 1.5, 6, and 12 m height, on the edge and interior of the mangrove. Results: A total of 382 specimens were collected, belonging to three subfamilies, 25 genera, and 36 species; Laminae was the subfamily most diverse with 24 species, followed by Cerambycinae with 11 species. At the edge of the mangrove 31 species were captured, and 21 in the interior. The 1D index determined that the edge was 2.51 more diverse than the interior, with a similarity of 61 %, sharing 16 species. The fluctuation of the communities on the edge and interior presented remarkable differences during the sampling year. On the edge, the greatest species richness was recorded at 6 m height and in the interior at 1.5 m and 6 m. Conclusions: Studies related to the vertical distribution of this group of insects, together with the increase in collection time and using complementary techniques, could give better results to inventory a larger number of species in the ecosystems.